Dopaminergic modulation of semantic network activation - Kischka, Udo; Kammer, Thomas; Maier, Sabine; Weisbrod, Matthias; Thimm, M.; Spitzer, Manfred (Neuropsychologia, 1996)
In order to examine the effect of dopamine on semantic processing, we performed a double-blind, placebo-controlled study. Healthy volunteers (n = 31) were tested in a lexical decision paradigm after ingestion of either l-dopa 100 mg with benserazide 25 mg or placebo. While direct semantic priming was influenced only marginally by l-dopa, the indirect priming effect was reduced significantly. These data support the hypothesis that dopamine increases the signal-to-noise ratio in semantic networks by reducing the spread of semantic processing, thereby leading to a focussing of activation.